2006
DOI: 10.1007/s10519-005-9040-9
|View full text |Cite
|
Sign up to set email alerts
|

Academic Impairment is the Most Frequent Complication of Neurofibromatosis Type-1 (NF1) in Children

Abstract: Neurofibromatosis type-1 (NF1) is a common genetic disorder associated with a variety of medical complications, cognitive impairments, and behavioral problems. One hundred and sixteen patients with NF1 (62 males, 54 females; mean age 12.4 years) and 80 typically developing children of the same ages (46 males, 34 females; mean age 11.5 years) were studied in terms of complications and learning impairment (one or more grade repetitions or school exclusion). Seventy of 116 patients had significant learning impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…To determine whether sex influences the outcome of murine optic glioma, we leveraged an Nf1 GEM strain that develops optic nerve/chiasmal gliomas ( Nf1 -CKO) 14,15 . While optic nerve volumes were indistinguishable between male and female Nf1 -CKO mice (Fig 2A), only female Nf1 -CKO mice exhibited reduced visual acuity on VOS testing (Fig 2B).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether sex influences the outcome of murine optic glioma, we leveraged an Nf1 GEM strain that develops optic nerve/chiasmal gliomas ( Nf1 -CKO) 14,15 . While optic nerve volumes were indistinguishable between male and female Nf1 -CKO mice (Fig 2A), only female Nf1 -CKO mice exhibited reduced visual acuity on VOS testing (Fig 2B).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Previous studies have shown that the most common psychoeducational problems include visual-perceptual-motor delay and spelling and arithmetic disabilities. 4,9 There is also an increased prevalence of Attention deficit disorder and attention deficit hyperactive disorder in this population. [10][11][12][13] In addition to these impairments, children with neurofibromatosis type 1 frequently demonstrate developmental delays.…”
mentioning
confidence: 99%
“…3,4 Visual-spatial deficits and difficulties with complex motor tasks are commonly seen in individuals with neurofibromatosis type 1 and can be considered hallmark features of neuropsychological impairment in children with neurofibromatosis type 1. [4][5][6][7] At the cellular level, understanding of the underlying genetic defect in neurofibromatosis type 1 has become central to understanding the varied clinical spectrum of disease. The protein product of the neurofibromatosis type 1 gene, neurofibromin, is expressed in many tissues, including neurons, oligodendrocytes, and other nonneural cell types.…”
mentioning
confidence: 99%